Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications. (2nd June 2020) - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, Manohar V.; Marathe, Yogesh N.; Bohara, Raghvendra A.
Abstract : Biocompatible and biodegradable polymers for designing wound dressing materials. Abstract : Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibers via an electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV–PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV–PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positive Staphylococcus aureus (NCIM 2654) and Gram-negative Pseudomonas aeruginosa (NCIM 5032), which are the main bacteria found in wound infections. The PHBV–PEO–ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs. In vitro cytotoxicity assays revealed the non-toxic nature of the prepared PHBV–PEO–ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.